2013
DOI: 10.1155/2013/179427
|View full text |Cite
|
Sign up to set email alerts
|

The Photocatalytic Property of Nitrogen-Doped TiO2Nanoball Film

Abstract: TiO2nanoball films of nitrogen doping and no doping were prepared by anodic oxidation method. The nitrogen-doped samples exhibited significant enhanced absorption in visible light range, narrowing band gap from 3.2 eV to 2.8 eV and the smaller nanoball diameter size. The concentrations of methyl blue reduce to nearly 44% after 4-hour photodecomposition test by nitrogen-doped sample. It is indicated that there may be two main reasons for the enhanced photocatalytic activity: the increase of O vacancy and photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The red shift is thought to be C, N, and S doping to TiO 2 matrix, narrowing the band gap energy of the TiO 2 due to the occurrence of the hybridized states located in the band gap [31] or tetracyine as photosensitizer. The photoluminescence (PL) is widely used to study the recombination of photo- Journal of Nanomaterials induced electron/hole pairs.…”
Section: Resultsmentioning
confidence: 99%
“…The red shift is thought to be C, N, and S doping to TiO 2 matrix, narrowing the band gap energy of the TiO 2 due to the occurrence of the hybridized states located in the band gap [31] or tetracyine as photosensitizer. The photoluminescence (PL) is widely used to study the recombination of photo- Journal of Nanomaterials induced electron/hole pairs.…”
Section: Resultsmentioning
confidence: 99%
“…N 1s XPS peaks at a binding energy in the range of ~396-400 eV showed different oxidative states of the N species. By the combination of the DFT calculations [31], it was identified that the N 1s XPS peaks at ~396-397 eV are due to the substitution of N with the lattice O of TiO2 [13,34], while those at ~399-400 eV are due to the interstitial N in the form of NOx or NHx [13,31,35,36]. [34], and (b) N-doped TiO2 prepared by the sol-gel method [36].…”
Section: Xps Spectramentioning
confidence: 99%
“…XPS [I] and UV-vis absorption spectra [II] of (a) N-doped TiO 2 nanoball film[34], and (b) N-doped TiO 2 prepared by the sol-gel method[36].…”
mentioning
confidence: 99%
“…Moreover, the samples TiNO/10 and TiO/20 present a preferential texture along the <004> plane. On the other hand, the peaks at 37.80°, 43.30°, and 62.80° visible in the diffractogram of the TiO 2 film deposited in CH 4 (TiC/5 film) could be related to <004>, <002>, and <202> planes of TiO phase indicating the formation of a substoichiometric compound [53] or even Ti crystalline phase [29,54,55]. It is obvious that pure methane used in PLD prevents anatase formation providing oxygen atoms deficiency.…”
Section: Nitrogen-doped Tio 2 Filmsmentioning
confidence: 99%